2015
DOI: 10.1088/1741-2560/12/3/036002
|View full text |Cite
|
Sign up to set email alerts
|

Compliant intracortical implants reduce strains and strain rates in brain tissuein vivo

Abstract: Objective The objective of this research is to characterize the mechanical interactions of (1) soft, compliant and (2) non-compliant implants with the surrounding brain tissue in a rodent brain. Understanding such interactions will enable the engineering of novel materials that will improve stability and reliability of brain implants. Approach Acute force measurements were made using a load cell in n=3 live rats, each with 4 craniotomies. Using an indentation method, brain tissue was tested for changes in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 63 publications
1
82
0
Order By: Relevance
“…To definitively prove this hypothesis, the diameter and surface chemistry of the implants were kept similar, enabling this study to specifically investigate the mechanical influence from other factors that could impact tissue response. Several studies have tried to compare the neural tissue reactions of flexible versus stiff implants, but these studies failed to control for the size of the implants or surface chemistry or both, making it difficult to draw conclusions [88,89]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To definitively prove this hypothesis, the diameter and surface chemistry of the implants were kept similar, enabling this study to specifically investigate the mechanical influence from other factors that could impact tissue response. Several studies have tried to compare the neural tissue reactions of flexible versus stiff implants, but these studies failed to control for the size of the implants or surface chemistry or both, making it difficult to draw conclusions [88,89]. …”
Section: Discussionmentioning
confidence: 99%
“…We postulate that when traditional stiff devices are used a significant amount of strain is caused by the horizontal displacement of the brain against the skull-anchored implant [88,89,95,96] while soft wires can dampen this effect [88]. In the representative images, the asymmetrical distribution in the cell shape distortion (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A biomimetic approach inspired by the structure of the dermis of the sea cucumber led to a mechanically adaptive material that can switch from a stiff and dry form (with a GPa-range Young's modulus) to a soft matrix (with a MPa-range Young's modulus) after a 10-20-minute insertion in a physiological environment 90 . The nanocomposite of a poly(vinyl acetate) matrix reinforced with rigid cellulose nanocrystals can also be machined in shank-like arrays with ~100-μm 2 cross-section that can be inserted through the pia mater of the cortex of rats without assistive surgical devices 91 . Systematic evaluation of the neuroinflammation response to these mechanically adaptive probes during a 16-week implantation demonstrated that over time, and in contrast to chemically matched but stiff probes (FIG.…”
Section: Mechanical Coupling Of Penetrating Electrodesmentioning
confidence: 99%
“…8). We have previously shown that our NC implants reduce the neuroinflammatory response compared to traditional silicon implants, at the most chronic time points (16 weeks) post-implantation [21,22,33,61]. Therefore, our goal in the design of the combinatory antioxidant and compliant implant approach was to maintain the reduced neuroinflammatory response throughout the duration of implantations, thereby allowing for stable recordings throughout implant lifetime.…”
Section: Discussionmentioning
confidence: 99%